A framework for firm-level critical material supply management and mitigation. (March 2019) - Griffin, Gillian; Gaustad, Gabrielle; Badami, Kedar
Abstract: Organizations of all sizes are vulnerable to critical material supply disruptions. Although there is a significant body of literature that examines how large entities such as nations and governments can assess and mitigate criticality, there is very little work that addresses firm-level criticality in a way that is actionable for businesses. This work uses literature review and case study analysis to understand the impact of critical material supply risk at the firm level, and to determine salient internal indicators. A total of 42 criticality studies were reviewed and the findings were used to develop a matrix to assess and monitor criticality risk using internal firm-specific data. The matrix incorporates three categories of risk including product concept viability, production, and profitability. It also contains four key business functions including finance, procurement, marketing, and production. These aspects were chosen because they are relevant to all businesses that produce and sell manufactured goods, and because they represent dynamics that are within the control of an individual firm. Unlike the global and national level indicators emphasized in most current research, the indicators proposed in this research are derived from data that firms can compile with reasonable ease. Finally, this work considers the role of the organization in criticality risk assessment and mitigation through an examination of the data needed to complete the aforementioned matrix and the likely sources of that information. The findings of this analysis elucidate the gap between internal and external and micro- and macro- criticality assessment, as well as provide a framework for firm-level criticality mitigation. Highlights: Firm-level criticality assessment can result in actionable strategies for supply risk mitigation. Supply disruptions have firm-wide impacts so vulnerabilities and remedies should be addressed cross-functionally. Manufacturing firms using critical materials are vulnerable to production cost increases that may impact firm performance. Firms can use internal indicators to tailor criticality assessment.